Biomechanical Comparison of Locking Versus Non-Locking Plates in Distal Femur Fractures - Khawand Bakhsh, M Aslam Mengal, Muhammad Tariq Hasani (Pakistan Journal of Medical & Health Sciences, 2023)
Background: To compare the ‘biomechanical performance, radiographic healing, and functional outcomes of locking versus non-locking plates in the surgical fixation of distal femur fractures’. Methods: This prospective comparative study was conducted at the Department of Orthopaedic Surgery, Bolan Medical Complex Hospital, Quetta, from January 2022 to June 2023. A total of 57 adult patients with distal femur fractures were included, with 29 managed using locking plates and 28 with non-locking plates. Primary outcome was time to radiographic union. Secondary outcomes included knee range of motion, KOOS score, pain level, malalignment, and complication rates. Data were analyzed using SPSS version 26, with p < 0.05 considered statistically significant. Results: The locking plate group demonstrated a significantly shorter mean time to union (17.3 ± 3.2 weeks vs. 19.5 ± 3.7 weeks, p = 0.02) and greater mean knee flexion at one year ‘(118.4° ± 8.6° vs. 112.2° ± 9.1°, p = 0.01)’. ‘KOOS scores were also higher in the locking plate group (78.6 ± 6.3 vs. 74.1 ± 6.8, p = 0.02)’. There was no significant difference in malalignment, delayed union, or infection rates. Implant failure occurred only in the non-locking plate group. Conclusion: Locking plates provided faster fracture healing and better functional outcomes compared to non-locking plates, without increasing complication rates. Their use is particularly beneficial in comminuted fractures, poor bone quality, and cases requiring early mobilization. Keywords: Distal femur fracture, Locking plate, Non-locking plate, Biomechanical stability, Functional outcome, Fracture union